The Patience of Growing and Maturing. From the Newly-made Man to the Perfect Man, in Irenaeus of Lyon - Namikawa, Miyako (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
According to Irenaeus of Lyon, in Adversus Haereses, the human being is only a «newly-made» creature who needs to grow slowly to become perfect. The study of these texts has relevance, sustains echoes, and can shed light on the way we articulate anthropology, theology, and Christology today. Instead of being a moral category, perfection consists of a free participation in the Life of God. In order to realize God’s plan for creation-salvation, both the human being and God become accustomed to each other. Created in the image of Christ who is the image of God, and in the likeness of God in so far as one receives the Spirit, the mystery of the human being’s original vocation is made visible in the mystery of Christ’s life. Time —including all other forms of human contingency as a creature— is contemplated from this perspective of progress and growth.